Sigmund freud, the education and the children - Lajonquière, Leandro de (Clinical Styles. The Journal on the vicissitudes of childhood, 2002)
Is it possible to apply psychoanalisis to education in terms ot neurosis prophylaxis and civilization action? In the works of Freud, this question hesitates between the necessary and contingent, constitued by political, social and religious conditions of this time.